Pengaruh bahan water repellent terhadap morfologi dan sifat-sifat fisika pada pembuatan kulit atasan sepatu ramah lingkungan - Prayitno Prayitno; Emiliana Kasmudjiastuti; Dona Rahmawati (Majalah Kulit, Karet, dan Plastik, 2016)
The term of eco-friendly leather can be interpreted as chrome-free tanned leather. Recently, almost 80% of leather is tanned using chrome tanning agent because of the ease in processing and excellence of the physical properties. Nevertheless, people nowadays want an eco-friendly leather product. Vegetable tanning materials can be said as eco-friendly tanning material because their waste degrades easily. One of the weaknesses in the use of vegetable tanning is a high water absorption capability. In this research used a water repellent material that has the properties to suppress the ability of water absorption. The purpose of the research was to determine the effect of water repellent on physical properties and morphology of leather tanned by vegetable tanning materials. Because one of the weaknesses in the vegetable tanning is its high water absorption capability, in this research, water repellent was used and varied by 5; 7.5; 10; 12.5; and 15% . Physical properties obtained were compared with analysis of variance with the significance level of 95%. The water repellent increased from 5% to 15%. The results showed a decrease in water absorption capability from 77.6% to 65.39%, tearing strength from 41.64 to 20.05 kg/cm, tensile strength from 227.10 to 163.53 kg/cm2, and elongation at break from 57.11 to 49.68%, strong swelling and WVA have no significant changes, while for WVP, the maximum use of water repellent at 12.5%. SEM results indicate the presence of a thin layer on the leather fiber that can inhibit the absorption of water.Keywords: water repellent, upper leather, vegetable tanning, water absorption.